Impact of HPV test results and emotional responses on psychosocial burden among Taiwanese women: a cross-sectional study - Chia-Chun Li; Ting-Chang Chang; Chun-Hsia Huang; Chi-Wen Chang; Yun-Fang Tsai; Lynn Chen (BMC Women's Health)
Abstract Background HPV is a sexually transmitted virus and is the cause of virtually all cervical cancers. Women undergoing HPV testing may experience significant psychosocial burdens, particularly those with a higher negative affect who test positive for the virus. This study investigates the relationships among test results, anxiety/depression, positive affect (PA), negative affect (NA), and psychosocial burden in women receiving their HPV test reports. Methods This was a cross-sectional, observational study design. The data were collected after women received their HPV test reports. A total of 273 women were recruited for this survey study from June 2018 to April 2020 in a medical center in North Taiwan. Data were collected on an author-designed demographic-disease survey, the European Quality of Life Index Version 5D 5-Level–Anxiety/Depression, the International Positive and Negative Affect Schedule–Short Form, and the HPV Impact Profile questionnaire. Data were analyzed by descriptive statistics, independent-sample t-tests, analysis of variance, Pearson correlations, and hierarchical multiple linear regression models. Results Among 273 women, 171 (62.6%) received HPV-positive results. Women with positive HPV test results reported significantly higher levels of anxiety/depression and NA compared to those with negative results. Additionally, those with positive results experienced greater psychosocial burden and worse sexual impact. Furthermore, age, NA, and PA were significant predictors of psychosocial burden in women who tested positive for HPV. Specifically, younger age, higher NA, and lower PA were significantly associated with increased psychosocial burden in women who received positive test results. Conclusion Health-care providers should pay attention to the test results and women’s emotional status, especially for women who have positive results and exhibit negative moods. To alleviate the psychosocial burden in women who have positive test results and high negative moods, professionals could provide timely HPV information and reserve time for women to ask questions, which could decrease their distress after receiving the report.